Representation of Local Government Interests and the Legislative Process - Wojciech Orłowski (Barometr Regionalny, 2018)
The basic principle of the functioning of local self-government is its independence, which is limited by the applicable law created in accordance with the principle of subsidiarity. The article analyzes the normative acts concerning the participation of local self-government bodies in the law-making process. Observation of the practice of their application leads to the conclusion that these solutions are not effective, and they do not correspond to the constitutional guarantees of the territorial self-government system position. The conclusions propose a new mode of selecting the Polish Senate and Self-Government Commission as well as the Polish delegation to the EU Committee of the Regions, which could improve the influence of territorial self-government bodies and the quality of solutions adopted in legal acts.